1997
DOI: 10.1016/s0092-8674(00)80506-1
|View full text |Cite
|
Sign up to set email alerts
|

PHYL Acts to Down-Regulate TTK88, a Transcriptional Repressor of Neuronal Cell Fates, by a SINA-Dependent Mechanism

Abstract: We show that Tramtrack (TTK88) expression represses neuronal fate determination in the developing Drosophila eye. Phyllopod (PHYL) acts to antagonize this repression by a mechanism that requires Seven In Absentia (SINA) and is associated with decreased TTK88 protein levels, but not reduced ttk88 gene transcription or mRNA stability. We present evidence that SINA, PHYL, and TTK88 physically interact and that SINA interacts genetically and physically with UBCD1, a component of the ubiquitin-dependent protein deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
239
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(247 citation statements)
references
References 63 publications
7
239
0
1
Order By: Relevance
“…These studies support our current results that Siah1 expression itself may influence the progression of NPC. Siah might serve a similar role as a downstream pathway component essential for oncogenic Ras signal as described in Drosophila [10,26,27]. Since Ras signal closely associated with cancer progression and transformation, such signal cascade may affect tumour progression by Siah1 as well as in human.…”
Section: Discussionmentioning
confidence: 88%
“…These studies support our current results that Siah1 expression itself may influence the progression of NPC. Siah might serve a similar role as a downstream pathway component essential for oncogenic Ras signal as described in Drosophila [10,26,27]. Since Ras signal closely associated with cancer progression and transformation, such signal cascade may affect tumour progression by Siah1 as well as in human.…”
Section: Discussionmentioning
confidence: 88%
“…As described above, activation of Notch prevents R7 from assuming the R1/R6 fate. One important function of RTKs in the presumptive R7 is to activate an E3 Ligase complex composed of Seven in absentia (Sina), Phyllopod (Phyl), and Ebi (Li et al, 1997;Tang et al, 1997;Dong et al, 1999;Boulton et al, 2000;Li et al, 2002). This E3 complex ubiquitinates Tramtrack88 (Ttk88), a transcriptional repressor, targeting it for proteolysis.…”
Section: Photoreceptor R7mentioning
confidence: 99%
“…Studies on photoreceptor cell differentiation of the Drosophila eye have shown that activation of the Ras/Map kinase-signaling cascade results in the ubiquitin-mediated degradation of Tramtrack (TTK) Tang et al 1997), a transcriptional repressor of neuronal cell fates, as well as of the transcription factor YAN (Rebay and Rubin 1995), a general inhibitor of differentiation of many cell types in the Drosophila eye. Therefore, we examined whether the Bcr-Abl-mediated down-regulation of Abi expression is Ras dependent.…”
Section: Bcr-abl-mediated Down-regulation Of Abi Expression Is Ras Inmentioning
confidence: 99%